2018
DOI: 10.1177/0885328218771195
|View full text |Cite
|
Sign up to set email alerts
|

Influence of citric acid on the physical and biomineralization ability of freeze/thaw poly(vinyl alcohol) hydrogel

Abstract: This work reports the modification of freeze/thaw poly(vinyl alcohol) hydrogel using citric acid as the bioactive molecule for hydroxyapatite formation in simulated body fluid. Inclusion of 1.3 mM citric acid into the poly(vinyl alcohol) hydrogel showed that the mechanical strength, crystalline phase, functional groups and swelling ability were still intact. Adding citric acid at higher concentrations (1.8 and 2.3 mM), however, resulted in physically poor hydrogels. Presence of 1.3 mM of citric acid showed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The broad absorption peak in the wavenumber range of 3275–3300 cm –1 was observed in all the samples, which can correspond to inter/intramolecular hydrogen bond stretching. , The width of the O–H stretching decreased with a corresponding decrease in the PVA concentration in hydrogels (Figure a). An absorption peak near the 1141 cm –1 wavenumber is attributed to the C–C stretching vibration as well as a characteristic of PVA crystallinity. , The presence of the peak at 1141 cm –1 in PVA/SPI hydrogels indicates the crystalline domain of PVA in hydrogels. The individual peaks at 1087, 1326, 1417, and 2944 cm –1 correspond to the C–O stretching vibration, C–C stretching, C–H bond, and C–H stretching, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The broad absorption peak in the wavenumber range of 3275–3300 cm –1 was observed in all the samples, which can correspond to inter/intramolecular hydrogen bond stretching. , The width of the O–H stretching decreased with a corresponding decrease in the PVA concentration in hydrogels (Figure a). An absorption peak near the 1141 cm –1 wavenumber is attributed to the C–C stretching vibration as well as a characteristic of PVA crystallinity. , The presence of the peak at 1141 cm –1 in PVA/SPI hydrogels indicates the crystalline domain of PVA in hydrogels. The individual peaks at 1087, 1326, 1417, and 2944 cm –1 correspond to the C–O stretching vibration, C–C stretching, C–H bond, and C–H stretching, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Although no significant difference in contact angles was observed between the PAA and TF groups, significant differences were observed when comparing these two groups to the PVA and IDN groups. According to previous studies, 44,45 it was suggested that the presence of polar hydroxyl and carboxylic groups would increase the surface wettability, whereas the presence of crosslinking agents in the PAA may lead to the changes in the surface morphology causing the increase in the contact angle.…”
Section: Resultsmentioning
confidence: 97%
“…The water contact angle (WCA) was used to measure the hydrophilicity of materials by capturing the image ( Figure 8 ) [ 49 ]. As shown in the WCA values, all samples, except PIP-N3, had a WCA less than 90°, indicating their hydrophilic nature.…”
Section: Resultsmentioning
confidence: 99%